1999
DOI: 10.1007/s007050050660
|View full text |Cite
|
Sign up to set email alerts
|

Apple chlorotic leaf spot virus 50 kDa protein is targeted to plasmodesmata and accumulates in sieve elements in transgenic plant leaves

Abstract: We investigated the in situ localization of the 50 kDa protein encoded by ORF2 of Apple chlorotic leaf spot virus (ACLSV) genome which is thought to be a movement protein. In immunogold electron microscopy of ACLSV-infected Chenopodium quinoa leaves, the 50 kDa protein was localized on plasmodesmata and nearby cytoplasm. Observation of transgenic Nicotiana occidentalis leaves expressing the 50 kDa protein fused to enhanced green fluorescent protein (EGFP) by fluorescence and confocal laser scanning microscopes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
8
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 32 publications
1
8
0
Order By: Relevance
“…A limited number of microscopic and physiological techniques have been used to provide more evidence for plasmodesmal association, in addition to observing GFP fusion proteins. Co‐localization with the polysaccharide callose, which is deposited at the necks of plasmodesmata (Radford et al , 1998), is a commonly used technique, involving either fluorescence immunolocalization (Blackman et al , 1998; Baluska et al , 1999; Yoshikawa et al , 1999; Erhardt et al , 2000) or staining with aniline blue (Gorshkova et al , 2003; Sagi et al , 2005; Levy et al , 2007). Ultimately, immunogold transmission electron microscopy with antibodies against either the protein of interest (Epel et al , 1996; Blackman et al , 1998; Grieco et al , 1999; Yoshikawa et al , 1999) or its GFP tag (Medina‐Escobar et al , 2003) is the most definitive technique available for confirming plasmodesmal association.…”
Section: Resultsmentioning
confidence: 99%
“…A limited number of microscopic and physiological techniques have been used to provide more evidence for plasmodesmal association, in addition to observing GFP fusion proteins. Co‐localization with the polysaccharide callose, which is deposited at the necks of plasmodesmata (Radford et al , 1998), is a commonly used technique, involving either fluorescence immunolocalization (Blackman et al , 1998; Baluska et al , 1999; Yoshikawa et al , 1999; Erhardt et al , 2000) or staining with aniline blue (Gorshkova et al , 2003; Sagi et al , 2005; Levy et al , 2007). Ultimately, immunogold transmission electron microscopy with antibodies against either the protein of interest (Epel et al , 1996; Blackman et al , 1998; Grieco et al , 1999; Yoshikawa et al , 1999) or its GFP tag (Medina‐Escobar et al , 2003) is the most definitive technique available for confirming plasmodesmal association.…”
Section: Resultsmentioning
confidence: 99%
“…(i) The amino acid sequence of 50KP has some similarity to MPs of other plant viruses and the protein was detected in the cell wall fraction from infected tissues (Sato et al , 1993 , 1995 ). (ii) Immunoelectron microscopy with an antiserum against 50KP showed that the protein is localized to plasmodesmata in infected Chenopodium quinoa cells (Yoshikawa et al , 1999 ). (iii) In transgenic plants expressing 50KP fused to GFP, the fluorescence was associated with plasmodesmata and accumulated in sieve elements (Yoshikawa et al , 1999 ).…”
Section: Introductionmentioning
confidence: 99%
“…The MP has been assigned to the '30K superfamily' by comparative sequence analyses (Mushegian & Koonin, 1993). Immunoelectron microscopy with antiserum against the MP showed that the protein is localized to plasmodesmata within virus-infected cells without the formation of tubules; virions were not observed in cell-wall plasmodesmata (Sato et al, 1995;Yoshikawa et al, 1999), although tubular structures protruded from the cell surface when MP fused to green fluorescent protein (MP-GFP) was expressed transiently in protoplasts (Satoh et al, 2000).…”
mentioning
confidence: 99%